2018
DOI: 10.1590/1980-549720180005.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Idosos não japoneses, japoneses e descendentes de japoneses no Estudo Saúde, Bem-Estar e Envelhecimento: condições funcionais e de saúde

Abstract: RESUMO: Introdução: A cidade de São Paulo conta com a maior comunidade de descendentes japoneses fora do Japão. Objetivos: Comparar as condições demográficas, econômicas, funcionais e de saúde de idosos não japoneses, japoneses e descendentes de japoneses, bem como analisar comparativamente as condições funcionais e de saúde de idosos nascidos no Japão e de seus descendentes nascidos no Brasil. Métodos: Estudo transversal realizado no município de São Paulo, no ano de 2010, com 1.345 idosos (≥ 60 anos) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Os demais estudos propuseram alternativas diferentes para o controle da PA, como a realização de sessões de acupuntura (Pereira et al, 2018;Bautista et al, 2011), intervenção psicológica (Pugliese et al, 2007, hipnose (Fernández et al, 2003), musicoterapia (Zanini et al, 2009 e até auto medida da PA objetivando o empoderamento para um maior controle da doença (Souza et al, 2012). Estudos demonstram que a participação do paciente com HA, no processo de tratamento da doença, ajuda a melhorar a qualidade de vida e controlar a PA deste Sakon, 2018;Pierin, 2016;Petroni et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os demais estudos propuseram alternativas diferentes para o controle da PA, como a realização de sessões de acupuntura (Pereira et al, 2018;Bautista et al, 2011), intervenção psicológica (Pugliese et al, 2007, hipnose (Fernández et al, 2003), musicoterapia (Zanini et al, 2009 e até auto medida da PA objetivando o empoderamento para um maior controle da doença (Souza et al, 2012). Estudos demonstram que a participação do paciente com HA, no processo de tratamento da doença, ajuda a melhorar a qualidade de vida e controlar a PA deste Sakon, 2018;Pierin, 2016;Petroni et al, 2018).…”
Section: Discussionunclassified
“…Não houve em nenhum dos estudos, comparativo quanto à raça ou etnia. Um estudo com idosos japoneses e descendentes de japoneses ilustrou bem esse fato, mostrando que o primeiro grupo apresentava um maior número de hipertensos, enquanto o segundo possua hábitos de vida mais saudáveis (Petroni et al, 2018), outro estudo apontou a etnia branca como tendo maior controle da PA (Menezes et al, 2016).…”
Section: Discussionunclassified
“…This large cross-sectional survey was conducted to investigate HTLV-1 infection in Brazil among the world's largest Japanese population outside of Japan. There are approximately 1.5 million people of Japanese descent in Brazil and most of them living in São Paulo state [17]. The prevalence of 5.1% (95% CI: 4.2-6.0) of HTLV-1 infection found in this study is higher than those observed in other studies conducted in different regions of the country considering HTLV-1 endemic a ´reas, including Salvador, the city with the highest HTLV-1 prevalence (1.48%) in Brazil [28][29][30][31], and higher than those conducted among specific risk groups, such as men who have sex with men, people who used illicit drugs, HIV-infected persons, and commercial sex workers, with prevalence rates varying from 0.7% to 3.0% [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…With the beginning of Japanese immigration to Brazil in 1908, mostly from provinces of Kumamoto, Hokkaido, Kagoshima, and Okinawa, Brazil is the country with the largest number of Japanese and their descendants outside of Japan. São Paulo state (Southeast region), followed by Parana ´(South region) and Mato Grosso do Sul (Central-West region) concentrate the largest number of Japanese and their descendants in Brazil [17]. In fact, HTLV-1 infection was first identified in Brazil, in 1986, among Japanese immigrants living in Campo Grande city, Mato Grosso do Sul state [18].…”
Section: Introductionmentioning
confidence: 99%